Trends in Convergence in EU. Differences between EU-10 and EU-15 - Lucian-Liviu Albu (European Regional Science Association (ERSA), 2013)
Early, the convergence theory was suggestively expressed in the Solow model. This can be shown in line with the fact that while economic development is advancing (expressed by the income per capita growth), on long run there is a general convergence process among countries. Generally, empirical evidences from the EU history have confirmed this process. Intuitively, some authors could consider that current crisis seems to affect convergence in EU. Contrary, how our analysis demonstrated, on long run the convergence process is not essentially altered. Depending on evaluation methodology, indicators used, and periods considered, the results of studies on convergence are often ambiguous. Despite a negative impact of actual crisis on growth rate, by using the Lorenz curve model and its derived Gini coefficients or variation coefficient, our study shows for the period of last decade a significant convergence in EU, in matter of GDP per capita. However, differences in matter of convergence still exist inside of groups of countries. Thus, generally while in EU-10 (last adhered countries to EU) is manifesting a strong convergence, in EU-15 (old members of EU) a significant trend of divergence was demonstrated. Moreover, besides GDP per capita, the convergence process is evaluated in case of other macroeconomic variables, like the export and import per capita, FDI per capita, etc. In specialised literature last time emerged some studies trying to estimate the so-called structural convergence. In our study, based on empirical evidences in spatial distribution of GDP per capita in EU we estimated a model to describe and simulate structural changes concomitantly with the general process of economic development. Using a set of adequate convergence indicators, we analysed the convergence process during last decade both at the EU level (EU-27), but also inside of the group EU-10 and inside of the group EU-15. As general conclusion, at the EU level a general tendency of structural convergence was demonstrated. However, between the two groups of countries, there were some different trends in matter of structural convergence.
Keywords: 330; spatial distribution; structural convergence; Lorenz curve; Gini coefficient; divergence